Sigma factors and promoters in Corynebacterium glutamicum - Pátek, Miroslav; Nešvera, Jan (Journal of biotechnology, 2011)
The Corynebacterium glutamicum genome codes for 7 sigma subunits (factors) of RNA polymerase (RNAP): primary sigma factor SigA (σ(A)), primary-like SigB and 5 other alternative sigma factors (SigC, SigD, SigE, SigH and SigM). Each sigma factor is responsible for recognizing promoters of genes belonging to a regulon (sigmulon) involved in specific functions of the cell. Most promoters of C. glutamicum housekeeping genes are recognized by RNAP+σ(A), whereas σ(B) is involved in transcription of a large group of genes active during the transition phase between the exponential and stationary growth phases when various stress factors threaten to damage the cell. The σ(H) regulon consists of the genes involved in heat shock response including those coding for regulators and other sigma factors. It seems therefore that σ(H) occupies a central position in the cross-regulated network of sigma factors and controls their concerted response to various stress conditions in C. glutamicum. The σ(M) factor was found to regulate genes responding to oxidative stress. The main role of σ(E) is to activate genes involved in response to a cell surface stress. Promoters of individual classes recognized by different sigma factors are compiled and the respective consensus sequences of their key recognition motifs (-35 and -10 regions) are derived. In a number of genes, two or more promoters controlled by the same or different sigma factors were discovered. These multiple, overlapping or dual promoters contribute to a complex gene transcription control mechanisms that integrate internal and external signals and tune gene expression in cells as required by environmental and physiological conditions.
Keywords: Stress, Physiological; Gene Expression Regulation, Bacterial; Base Sequence; Corynebacterium glutamicum; sekvence aminokyselin; genové regulační sítě; regulon; Molecular Sequence Data; sigma faktor; Gene Regulatory Networks; Amino Acid Sequence; regulace genové exprese u bakterií; fyziologický stres; molekulární sekvence - údaje; DNA-Directed RNA Polymerases; sekvence nukleotidů; DNA řízené RNA-polymerasy; Sigma Factor; promotorové oblasti (genetika); Promoter Regions, Genetic; Regulon